Estimating the travel demand impacts of semi automated vehicles. (June 2022) - Hardman, Scott; Chakraborty, Debapriya; Tal, Gil
Abstract: In this study we investigate changes in travel due to level 2 automation among owners of electric vehicles in California. Level 2 automation has the potential to reduce driver fatigue and make driving less stressful which could mean drivers choose to travel more. We use questionnaire survey data to investigate changes to long distance travel and annual vehicle miles travelled (VMT) due to automation. Results show those who report doing more long-distance travel because of automation are younger; have a lower household income; live in urban areas; own a longer-range electric vehicle; use automation in a variety of conditions; and have pro-technology attitudes and prefer outdoor lifestyles. We use propensity score matching to investigate whether automation leads to an increase in annual VMT. The results of this show 4059–4971 more miles per year among users of level 2 automation compared to owners of similar vehicles without automation.